2019
DOI: 10.21873/anticanres.13390
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minimally Invasive Surgery and Abdominal Surgery Among Patients With Cervical Cancer

Abstract: Materials andMethods: This retrospective analysis included all patients who received surgical treatment with curative intent between January 2011 and December 2017 for stages IA1 to IIB cervical carcinoma. Patients receiving primary or secondary surgery after neoadjuvant chemotherapy were also included. Results: In total, 75 patients were included, of whom 34 patients underwent minimally invasive surgery and 41 underwent open surgery. Neoadjuvant chemotherapy was performed in 10 patients in the minimally-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…The results of this study are consistent with those reported by Dominik R and Paika, but both studies were single‐center studies with fewer cases 23, 24 . This study used the advantage of a large number of cases from a large database of cervical cancer for 1:1 matching of the factors affecting the tumor prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study are consistent with those reported by Dominik R and Paika, but both studies were single‐center studies with fewer cases 23, 24 . This study used the advantage of a large number of cases from a large database of cervical cancer for 1:1 matching of the factors affecting the tumor prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…In neonates, it requires an extremely high level of expertise for both the surgeon and anesthesiologists. With this approach, an improved outcome was shown in other diseases (13)(14)(15). Enhanced recovery after surgery (ERAS) or 'fast-track' methods enable standardization of postoperative medical care, improvement of patient outcomes, promotion of early recovery, and reduction of healthcare expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in oncological outcomes between LRH and ARH are essential to consider and opinions vary from different studies (1, 920). After the consternation brought to light by the study of Ramirez et al (1), a prospective randomized international phase III trial, gynecologists began to think how do we proceed in the face of these data (33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in our review had to meet all of the following criteria: (a) uterine cervical cancer; (b) radical hysterectomy and lymphadenectomy; (c) data including the comparison of laparotomy and laparoscopy; (d) date including oncologic survival outcomes; (e) studies published in English. In total 13 articles were included (1, 920) with details shown in Supplementary Table 1.…”
Section: A Reviewmentioning
confidence: 99%